Examining malpractice in the education context - B. Calderon, Ameer Benjamin; Ancho, Inero V. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Malpractice is a dereliction of professional duty or a failure to exercise an ordinary degree of professional skill or learning by rendering professional services which results in injury, loss or damage. This study probed into the questions: (2)what are the types of educational malpractices in the Philippine education system; and (2) who are mostly guilty of these offenses? Data were gathered by downloading court cases and newspaper articles. A total of ten online court cases involving teachers, parents, students, school administrators, and principals were included. Coding was done by identifying the emerging themes per cluster. Findings indicated that offenses can be clustered into two: corruption and misconduct. Corruption cluster includes offenses ranging from illegal collection by the teachers from the students to the misuse of funds by the school administrators. On the other hand, the misconduct cluster includes sexual abuse targeted towards students by the teachers, and abuse of power by the school administrators towards the teachers. Data revealed that some cases involving principals whose offenses include misuse of funds and abuse of power were dismissed. Furthermore, involvement of principals was under-reported due to certain interfering reasons like fear, doubt or hesitation, or carelessness on the part of those who file the cases or as a result of the misleading or scheming practices of the offenders. On the other hand, abuses and minor offenses committed by the teachers were magnified. Among the teachers charged of malpractice in education, only one was found not guilty. This led to the creation of a typology that highlights the forms of offenses, the offenders and the offended as well as the results of the investigation of the cases. . Comparatively speaking, this may be attributed to the lack of power, authority and influence teachers have against principals and other school administrators.